Iran Economic Monitor, Fall 2021 : Adapting to the New Normal - A Protracted Pandemic and Ongoing Sanctions - World Bank (World Bank, Washington, DC, 2021)
Iran’s economy is gradually recovering following a lost decade (2011–2020) of negligible economic growth. Less stringent COVID-19 restrictions, adaptation to the new normal - reflected in a recovery in consumption, and more favorable oil sector conditions have driven a four-quarter rebound after June 2020, albeit from a low base. The rebound was boosted by the rapid rollout of COVID-19 vaccines in the second half of 2021/22. However, limited accessible foreign exchange reserves, due to ongoing US sanctions, have led to exchange rate volatility and a surge in inflation. The economic rebound has also been predominantly jobless which coupled with high inflation has translated to declining household welfare, especially among the bottom income deciles who were also disproportionately impacted by the pandemic. Meanwhile, adverse climate change events such as droughts and record temperatures have led to water shortages and energy blackouts which have brought the socio-economic urgency of these challenges to the fore.